O Programa Nacional de Alimentação Escolar (PNAE) no cotidiano de uma escola estadual em Alegre/ES. - Freitas, Josiano Silva (2022)
The research was a qualitative case study that analyses how the National School Feeding Program (PNAE) is understood by students living in the countryside at a state school in the city of Alegre/ES. The theoretical framework used was Historical-Critical Pedagogy, with Dermeval Saviani, the main author, in dialogue with other authors of critical theory: Gaudêncio Frigotto, Pablo Gentilli, Ricardo Antunes, among others. Data were collected through focus group interviews with students, and later analyzed using Content Analysis. The PNAE is understood by students mainly as an opportunity for energy supplementation, since they see the program from the point of view of food. They also highlighted the importance of food in the teaching and learning process in which they are part, however, they are unaware of food and nutrition education as a result of the actions to be developed by those responsible for the program. The way of preparing food was criticized by students, as well as the amount of food offered at school, as insufficient to meet their needs. This situation can be explained, among other factors, by the lack of a nutritional analysis that allows knowledge about the nutritional needs of students for the elaboration of the menu, since this is prepared by the Secretary of Education of the State of Espírito Santo (SEDU) without consider the characteristics of students use it in school spaces. As a result, the supply of food does not serve students satisfactorily, which highlights the interference of the weaknesses of outsourced management for the implementation of the PNAE guidelines and objectives in the lives of students living in the countryside. The research indicates the need to change the management processes of the PNAE in the school where the study was developed, since school meals have well-defined objectives to be achieved and, clearly, through the outsourced modality, this has not happened.